The microstructure evolving and element transport of Ni-based laser-cladding layer in supercritical water. (15th April 2022) - Ren, Lu; Ding, Yun; Cheng, Yanhai; Nong, Jing; Wang, Shuai; Wang, Shicheng; Zhang, Dongyang; Qin, Qiang; Si, Jiajia; Shoji, Tetsuo; Sun, Dongbai; Xu, Jian
Abstract: To improve the oxidation resistance of the low-cost materials in supercritical water (SCW), the mild steel surface was laser cladded with Ni-based alloy powder. The oxidation behavior of coated material was investigated in SCW. Consequently, because of the constrained melting and solidification, extensive microstructure changes. Crystals in different regions are transformed into equiaxed crystals, which enhances the interatomic bonding strength of the solid solution. Additionally, the Ni-based cladding layer has an observable growth direction near the fusion line and the oxidation reactions could be inhibited by the formed NiO and (Cr, Ni) solid solution. Highlights: The crystals in the Ni-Cr-Mo-Nb coating transform to equiaxial crystals. Element diffusion is limited from coating to substrate under SCW condition. Dendrites grow along the fusion line enhancing the bond ability in the SCW. AISI 1015 with Ni-Cr-Mo-Nb laser-cladding layer can be effective to SCWO resistance.